2015
DOI: 10.1002/qj.2649
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on the collective risk of extratropical cyclones

Abstract: In this study the dependence between the frequency and intensity of extratropical and intensity results in large biases in the variance and the extremes of the aggregate risk, especially over Scandinavia. Therefore including frequency intensity dependence in extratropical cyclone loss models is necessary to model the risk of extreme losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 42 publications
(101 reference statements)
1
29
0
Order By: Relevance
“…They showed that five teleconnection patterns are significant at the 5% level with regard to explaining the inter-annual variability: NAO, SCA, EA pattern, EA/WR and the Polar pattern (POL). More recently, Hunter, Stephenson, Economou, Holland, and Cook (2016) found a significant correlation between cyclone counts in Scandinavia and the SCA index. In terms of a physical link between large-scale patterns and European storminess, Woollings and Blackburn (2012) could detect an influence of the NAO and the EA on the location and strength of the North Atlantic jet stream which is in turn responsible for increased or decreased storminess during the European winter.…”
Section: Introductionmentioning
confidence: 93%
“…They showed that five teleconnection patterns are significant at the 5% level with regard to explaining the inter-annual variability: NAO, SCA, EA pattern, EA/WR and the Polar pattern (POL). More recently, Hunter, Stephenson, Economou, Holland, and Cook (2016) found a significant correlation between cyclone counts in Scandinavia and the SCA index. In terms of a physical link between large-scale patterns and European storminess, Woollings and Blackburn (2012) could detect an influence of the NAO and the EA on the location and strength of the North Atlantic jet stream which is in turn responsible for increased or decreased storminess during the European winter.…”
Section: Introductionmentioning
confidence: 93%
“…Investigations of multihazards can take a number of perspectives. Gallina et al (), Kappes et al (), Fuchs et al (), and Goddard et al (), amongst others, discuss the challenges of multihazard analysis in the context of two approaches: spatial focus (e.g., Hunter et al, ) versus a thematic focus (e.g., Gill & Malamud, ), and the difficulty associated with using climate information for risk management, vulnerability assessment, and decision making. Osgood et al () discuss the practicalities of using financial instruments for risk sharing in the context of ENSO impacts on agriculture in Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Hunter et al () addresses aggregate risk (the risk of multiple events within a season) for North Atlantic extratropical cyclones. They investigate the nature of joint forcings using a mathematical framework and look at five large‐scale flow patterns, including the NAO and the East Atlantic Pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Pinto et al, 2009). Furthermore, the NAO and other large-scale modes affect both the frequency and intensity of extratropical cyclones over the North Atlantic (Hunter et al, 2016). The existence of clustering has been associated with NAO variability (e.g.…”
Section: Introductionmentioning
confidence: 99%